Enhancing Students' Conceptual Understanding in History Education Through Canva-Assisted Interactive Learning Media - Sri Ika Faika; Sholeh Hidayat; Yuyu Yuhana (STAI Hubbulwathan Duri, 2025)
History learning is often perceived as monotonous due to the dominance of conventional lecture-based methods, resulting in students' low conceptual understanding. To address this issue, the study investigates the effectiveness of Canva as an interactive learning tool to enhance students’ understanding of historical concepts. This research employed a mixed-methods approach with both quantitative and qualitative data collection. The quantitative component involved a pre-test and post-test design with 34 eleventh-grade students at SMAN 2 Krakatau Steel Cilegon. Paired sample t-tests were conducted to measure significant changes in student understanding. The qualitative component included classroom observations and semi-structured interviews with students and teachers to explore user experiences and implementation challenges. The results showed a statistically significant improvement in students' understanding, with mean scores increasing from 65.32 (pre-test) to 82.47 (post-test) (p = 0.000). Observation data indicated higher student engagement: participation in discussions rose from 40% to 85%, and active questioning increased from 30% to 80%. Interview findings highlighted that Canva's visual features made historical content more accessible and engaging. Canva proved to be an effective digital tool for improving student comprehension and engagement in history learning. However, issues such as limited device access and internet connectivity were noted. While Canva shows promise in enhancing history education, its broader application requires further investigation across diverse educational contexts. This study contributes to the growing discourse on integrating technology into history learning in Indonesian secondary education.